Physicochemical properties of chili padi Centil (Capsicum frutescens) powder dried at different drying temperatures - Hussain, N.; Abd Rahim, N.A.; Azhar, N. (Rynnye Lyan Resources, 2020)
This study addressed selected drying temperatures in extending the shelf life of local chili padi Centil (Capsicum frutescens) powder with better physicochemical properties. The effects of drying at different temperatures (50˚C, 60˚C, and 70˚C) on chili padi Centil powder was evaluated through its functional properties, including moisture content, color, water holding capacity, oil holding capacity and water solubility index as well as total phenolic content determination. Chili padi Centil powder dried at 70˚C had permitted level of moisture content (10.38%). Drying treatment at 70˚C also produced significantly smaller particle size powder (1301.1821 μm) with higher water holding capacity (2.67%), oil holding capacity (1.3%) and water solubility index (7.65%) compared to chili padi Centil dried at 50˚C and 60˚C. The powder dried at 50˚C and 70˚C showed significant visible color difference where 50˚C drying temperature resulted in intense red color powder whereas 70˚C drying temperature resulted in degraded orange color powder. The drying treatment significantly degraded the total phenolic content of chili powder.